2020
DOI: 10.21203/rs.3.rs-41590/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Controlled Study on the Diagnostic Accuracy of Panoramic and Peri-Apical Radiography for Detecting Furcation Involvement

Abstract: Background: The aim of this study was to determine diagnostic accuracy, sensitivity and specificity of panoramic and peri-apical radiography for detecting furcation involvement (1) and to evaluate the possible impact of clinical experience on these diagnostic parameters (2).Methods: Periodontitis patients in need of an implant were retrospectively selected. Inclusion criteria were the presence of a CBCT, panoramic and peri-apical radiograph of the site of interest within a one-year time frame. All furcation si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This reflects the higher risk of tooth loss for FI degree III compared with degree I and II, 35 but potentially also the fact that in the present study furcation involvement was only estimated from a radiographic analysis, 46 so it may be subject to error 47 . Several studies have clearly reported that furcation assessment via two‐dimensional radiography has low sensitivity and should be accompanied by clinical detection for better accuracy 48,49 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This reflects the higher risk of tooth loss for FI degree III compared with degree I and II, 35 but potentially also the fact that in the present study furcation involvement was only estimated from a radiographic analysis, 46 so it may be subject to error 47 . Several studies have clearly reported that furcation assessment via two‐dimensional radiography has low sensitivity and should be accompanied by clinical detection for better accuracy 48,49 …”
Section: Discussionmentioning
confidence: 82%
“…47 Several studies have clearly reported that furcation assessment via twodimensional radiography has low sensitivity and should be accompanied by clinical detection for better accuracy. 48,49 The main strength of this study is the long-term followup period and analysis of a population not undergoing systematic periodontal therapy. The limitations of this study include the use of orthopantomograms, a questionable smoking definition (non-smokers included both who never smoked or smoked <10 cigarettes/day) and the lack of sample size calculation.…”
Section: Discussionmentioning
confidence: 99%
“…But predictable results have been still difficult to obtain due to the complex oral environment, which limited the prognosis. Previous clinical follow-up studies declared that patients received conventional treatment, comprising various types of access flaps and/or resection, were deeply troubled by probing depth reduction, hard tissue fill or even elimination of the intrabony component [22]. Furthermore, residual pockets often persisted following nonsurgical therapy or the use of access flaps, and resective techniques were associated with chronic loss of attachment and increases in soft-tissue atrophy [23].…”
Section: Discussionmentioning
confidence: 99%